Impact of FDI, COP, and Inflation to Export in Five ASEAN Countries - Nanda Adhi Purusa; Nurul Istiqomah (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2018)
The effects of foreign direct investment (FDI), crude oil price and inflation on the export are mainly examined in the case of Indonesia, Malaysia, Philippines, Thailand, and Vietnam by using data from 2000 to 2015. These countries have opportunity to increased prosperity in the ASEAN Economic Community (AEC). Therefore, increasing productivity and international trading are important for each country. This study employed panel data model in the analyses and the findings show that Fixed Effect Model with Generalized Least Square method is implemented.  Hence, using this method is determined by likelihood test and Hausman test. The statistical tests in this study consist of partial coefficient test, stimulant, and coefficient of determination. The result shows that FDI and crude oil price have positive effect and significant on export, but inflation has negative effect and significant on export. Constant value shows that each country has the difference condition. Simple bureaucracy is needed to increased efficiency that will attract foreign investors to invest their fund and the discovery of alternative energy and new production technique can increase a country productivity significantly in producing goods or services for both domestic and export-oriented.